One Health Aotearoa: a transdisciplinary initiative to improve human, animal and environmental health in New Zealand - Sarah Harrison; Michael G. Baker; Jackie Benschop; Russell G. Death; Nigel P. French; Garth Harmsworth; Robin J. Lake; Iain L. Lamont; Patricia C. Priest; James E. Ussher; David R. Murdoch (One Health Outlook, 2020)
Abstract There is increased recognition that complex health challenges at the human-animal-environmental interface require a transdisciplinary, “whole-of-society” approach. This philosophy is particularly pertinent in Aotearoa-New Zealand because of the country’s relatively isolated island ecosystem, economic reliance on agriculture and its intensification, and existing indigenous worldview that emphasises holism and interconnectivity between humans, animals and the environment. In New Zealand, the One Health Aotearoa (OHA) alliance was established in order to better connect researchers and to address a growing number of infectious diseases challenges. The emphasis of OHA is to bring together and facilitate interactions between people from diverse disciplines, link to stakeholders and communities, and engage with policy-makers, government operational agencies, and funders, thus providing a holistic and integrative systems-thinking approach to address priority questions and achieve desired outcomes in One Health. The initial focus of OHA has been on infectious diseases, but there is increasing recognition of the potential benefits of the alliance to address broader complex issues. Greater involvement and overlap of the environmental sciences, human and animal health sciences, social science, and indigenous kaupapa Māori research is particularly critical for ensuring its success within the New Zealand context. Given the economic and cultural importance of New Zealand’s “clean, green” image, a One Health approach that draws strongly on the environmental sciences makes particular sense. Furthermore, as the global environment becomes increasingly stressed by anthropogenic pressures our research may hold potential solutions for similar challenges elsewhere.